Performance evaluation of Badri cattle - JOSHI, PRAGYA; TIWARI, RUPASI; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2018)
The present study was carried out to assess the performance of the recently certified Badri cattle, which is adapted to the topography and climate of Uttarakhand. Performance of the cattle was measured using various traits, viz. milk yield/day (litres), lactation length (months), dry period (days), productive life (years), age at puberty (years), age at first calving (years), breeding capacity (number of calves born/cow), inter calving period (months), conception rate (number of services/conception), service period (months) and draught animal power. The study was conducted in 12 villages from 4 blocks of Almora and Pauri Garhwal district of Uttarakhand by personally interviewing 120 Badri cattle owners through semi structured interview schedule. There is no significant difference between the 2 districts with respect to various performance traits. The average milk yield/day/cow, lactation length, dry period and productive life were found to be 1.6±0.7 litre/day, 11.8±2.1 months, 1.9±0.7 months and 11.9±1.6 years, respectively. The average age at puberty, age at first calving, breeding capacity, inter calving period, conception rate and service period were observed to be 3.2±0.7 years, 4.3±0.7 years, 8.8±1.4 calves/cow in lifetime, 13.7±1.9 months, 1.4±0.6 service/conception and 4.7±1.9 months respectively. Average working days/year, average working hours/day and average area ploughed/day were 32.9±7.6 days/year, 3.9±0.9 h/day, 0.4±0.05 acres/day respectively. Keeping in view the lower performance of the Badri cattle there is need of improvement by starting various plan and strategies to spread the importance of nutrition and better management practices by the government, which will further encourage the people of hills to conserve the cattle along with increasing the viability and profitability of Badri cattle rearing among the marginal and landless farmers.